Submicrometer Epsilon-Near-Zero Electroabsorption Modulators Enabled by High-Mobility Cadmium Oxide - Salvatore Campione; Michael G. Wood; Darwin K. Serkland; S. Parameswaran; Jon Ihlefeld; T. S. Luk; Joel R. Wendt; Kent M. Geib; Gordon A. Keeler (IEEE Photonics Journal, 2017)
Epsilon-near-zero materials provide a new path for tailoring light–matter interactions at the nanoscale. In this paper, we analyze a compact electroabsorption modulator based on epsilon-near-zero confinement in transparent conducting oxide films. The nonresonant modulator operates through field-effect carrier density tuning. We compare the performance of modulators composed of two different conducting oxides, namely, indium oxide (In2O3 ) and cadmium oxide (CdO), and show that better modulation performance is achieved when using high-mobility (i.e., low loss) epsilon-near-zero materials such as CdO. In particular, we show that nonresonant electroabsorption modulators with submicron lengths and greater than 5 dB extinction ratios may be achieved through the proper selection of high-mobility transparent conducting oxides, opening a path for device miniaturization and increased modulation depth.